Stationary Josephson Effect in Junctions Made of d-Wave Superconductors with Charge Density Waves - Gabovich, A.M.; Li, M.S.; Szymczak, H.; Voitenko, A.I. (Металлофизика и новейшие технологии, 2013)
Dependences of the stationary Josephson current in symmetric and nonsymmetric tunnel junctions involving d-wave superconductors with charge density waves (CDWs) on the system parameters are calculated. Both the checkerboard and unidirectional CDW patterns are studied. The directionality of superconductive tunnelling was taken into account. As shown, CDWs can drastically influence the Josephson current, the changes being more significant in underdoped compositions. Розраховано залежности стаціонарних джозефсоновських струмів через симетричні та несимметричні тунельні переходи, що вміщують d-надпровідники з хвилями зарядової густини (ХЗГ), від параметрів цих надпровідників. Розглянуто гребінчасту та шахову конфігурації ХЗГ. Прийнято до уваги спрямованість тунелювання. Показано, що ХЗГ суттєво впливають на розглядуваний джозефсоновський струм, що повинно більш сильно проявлятися для високотемпературних надпровідників з рівнем леґування нижче за оптимальний. Рассчитаны зависимости стационарных джозефсоновских токов через симметричные и несимметричные туннельные переходы, содержащие d-сверхпроводники с волнами зарядовой плотности (ВЗП), от параметров этих сверхпроводников. Рассмотрены гребенчатая и шахматная конфигурации ВЗП. Принята во внимание направленность туннелирования. Показано, что ВЗП существенно влияют на рассматриваемый джозефсоновский ток, что должно сильнее проявляться для высокотемпературных сверхпроводников с уровнем легирования ниже оптимального.